Learning of Catholic theology in the digital age - Ngumba, Lelo J. (HTS teologiese studies, 2019)
This article focuses on the intersections between theological knowledge and the use of the Internet to access study resources for students studying Catholic theology at tertiary institutions. In the 21st century, the use of the Internet to access electronic resources (ERs) is gaining momentum as a tool for obtaining needed information among theology students, to support many aspects of their learning activities. This is mainly because of the proliferation of online theological libraries, as well as the fact that theology students ought to resist the easy path of uncritical passivity and select reliable data from other resources, and welcome it without merely imposing their critical theological opinions and views. Recent literature indicates that the hierarchical nature of Catholic doctrine needs not to exclude openness to the more rhizomatic approaches to knowledge structures that students’ independent accessing of online ER represents. This intersection in learning theology requires a theoretical paradigm shift for adult theology students which can contribute greatly to the enlargement of the theology students’ academic horizon and enriches their minds for an open theological dialogue and discussion with different theological opinions and views.